2017
DOI: 10.3389/fimmu.2017.01048
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the Vitamin D Receptor (VDR) Gene, Together with Genetic Variation, Race, and Environment Influence the Signaling Efficacy of the Toll-Like Receptor 2/1-VDR Pathway

Abstract: BackgroundThe disparity in prevalence of infectious diseases across the globe is common knowledge. Vitamin D receptor (VDR)-mediated toll-like receptor (TLR) 2/1 signaling produces antimicrobial peptides, which is critical as a first line of defense in innate immunity. Numerous studies disclosed the independent role of genetic polymorphisms in this pathway, vitamin D status or season and more recently epigenetics, as factors contributing to infectious disease predisposition. Few studies address the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 47 publications
3
30
0
1
Order By: Relevance
“…The SNP selection was determined by their relationship with vitamin D concentrations in pregnant women and its association with neonatal outcomes (Barchitta et al, ; Knabl et al, ). TaqI and ApaI are highly prevalent in populations with African ancestry (Meyer, et al, ), similar to the sample of this study (Lima‐Costa et al, )…”
Section: Methodssupporting
confidence: 87%
“…The SNP selection was determined by their relationship with vitamin D concentrations in pregnant women and its association with neonatal outcomes (Barchitta et al, ; Knabl et al, ). TaqI and ApaI are highly prevalent in populations with African ancestry (Meyer, et al, ), similar to the sample of this study (Lima‐Costa et al, )…”
Section: Methodssupporting
confidence: 87%
“…CYP27B1 catalyzes the de novo production of 1,25(OH) 2 D from accumulated 25(OH)D; 1,25(OH) 2 D is delivered to the cells via the vitamin D-binding protein (DBP), which is encoded by GC. The liganded VDR-transcription factor complex binds to vitamin D response elements (VDREs) in cathelicidin antimicrobial peptide (CAMP), activating CAMP expression [ 45 ]. The methylation level of CYP27B1 is elevated in primary lymphoma and leukemia cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether this subtle methylation difference could alter vitamin D metabolism and change macrophage M.tb killing capacity is not clear and needs more exploration. Other factors, such as genetic polymorphisms, sunlight exposure, food intake, and drug supplementation, can also affect vitamin D levels and the risk of TB [ 45 ]. Third, immune responses downstream of the vitamin D metabolic pathway should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Several studies have suggested that VDR gene methylation alterations may have a role in the pathogenesis of infectious and malignant diseases. [29][30][31][32][33][34] Vitamin D plays an important regulatory role in immune system 6 function and its deficiency has been introduced in the etiology of autoimmune diseases. 19,35 It affects many aspects of the innate and adaptive immune system.…”
Section: Introductionmentioning
confidence: 99%